Respon Fisiologi Sapi FH Laktasi dengan Substitusi Pakan Pelepah Sawit dengan Jumlah yang Berbeda - Ghiardien, A.; Purwanto, B. P.; Atabany, A. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2016)
This study was done to determine milk production and its quality of FH cows fed oil palm frond (OPF) for 3 months in UPT of Livestock Breeding Station Kampar Riau.This research used Fresh OPF chopping with different percentage as feed substitution in dairy feed to see the physiological responses of dairy cattle. The feeding treatments were 100% EG, 75% EG + 25% OPF, 50% EG + 50% OPF and 25% EG + 75% OPF. This research was designed by Latin Square Design (RBSL) and analyzed by ANOVA with physiological responses which is skin temperature, body temperture,rectal temperature, respiration, and heart rate as observed variables. The results showed that cage condition and environmental could potentially caused stress (THI : 68–90). chopping fresh OPF with different percentage subtitution did not signiicantly effect to physiological response except heart rate where the highest value is 75% OPF with 72,1±1,98 beat/min compared with control, 25% and 50%. Overall, OPF can be used as feed resourch subtitution because did not give a negative effect for physiological responses for dairy cattle.